Os efeitos na formação dos resultados contábeis a partir da nova realidade contábil brasileira introduzida pela lei 11.638/2007 e os esforços do país na harmonização dos princípios contábeis brasileiros com os internacionais - Sousa, Wiliam Calegari de (2012)
From 2007, the enactment of Laws 11.638/07 and 11.941/09 changed substantially from 2007, the accounting, presentation and dissemination of business entities financial statements established in Brazil, representing the Brazilian starting point of the convergence efforts and harmonization of local accounting methods with international accounting principles. The objective of this research project is to evaluate the publicly held company impact on profit & loss statements, resulting from the local accounting harmonization with the IAS on the early adoption of new accounting rules. This essay comprises data collection from the period between 2007 and 2009 for 57 (fifty seven) financial statements , as per São Paulo Stock Exchange Index Ibovespa on January 03, 2011; with exception of financial institutions that were partially already under the new rules as determined by the Central Bank of Brazil. In addition to demonstrate the income statement effects on the surveyed entities, it is also listed the main accounting adjustments that caused those differences on the 10 (ten) larger variations observed in the sample